KEBIJAKSANAAN APBD DAN KESEJAHTERAAN MASYARAKAT DI PROVINSI SULAWESI SELATAN - Kusreni, Sri (Program Doktor Ilmu Ekonomi, 2009)
Study on the policy of APBD and its implication toward the welfare of people in South Sulawesi is aimed at analyzing and searching the influence of local fiscal capacity, capital expenditure and budgeting toward the welfare of the people. Data of this study is quantitatively analyzed by regression. The result points up that: (1) local fiscal capacity and allocation of capital expenditure have positive correlation and significant influence toward the welfare of the people; (2) budgeting has negative correlation and insignificant influence toward the welfare of the people; (3) 23.1 percent of the welfare of the people is significantly influenced by the variables of the policy of APBD, while the rest is influenced by other variables outside the model; and (4) fiscal capacity has larger influence toward the welfare of the people than local capital expenditure. Keywords: fiscal capacity, local government expenditure, budgeting and welfare.